(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article emphasizes that the formation and development of pottery in Uzbekistan in ancient times laid a solid foundation for the emergence of regional pottery schools in subsequent historical periods. Specifically, it notes that the technological expertise, decorative traditions, formal compositions, and aesthetic views that developed during this period directly influenced the flourishing of medieval pottery.